2000
DOI: 10.1016/s1097-2765(00)00057-5
|View full text |Cite
|
Sign up to set email alerts
|

Rad54 Protein Is Targeted to Pairing Loci by the Rad51 Nucleoprotein Filament

Abstract: Rad51 and Rad54 proteins are important for the repair of double-stranded DNA (dsDNA) breaks by homologous recombination in eukaryotes. Rad51 assembles on single-stranded DNA (ssDNA) to form a helical nucleoprotein filament that performs homologous pairing with dsDNA; Rad54 stimulates this pairing substantially. Here, we demonstrate that Rad54 acts in concert with the mature Rad51-ssDNA filament. Enhancement of DNA pairing by Rad54 is greatest at an equimolar ratio relative to Rad51 within the filament. Recipro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
195
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 172 publications
(215 citation statements)
references
References 55 publications
17
195
2
Order By: Relevance
“…The ATPase and DNA supercoiling activities are up-regulated upon complex formation with Rad51 (Mazin et al 2000a;Van Komen et al 2000). Consistent with the results from the affinity pull-down experiments (Fig.…”
Section: Hed1 Ablates Functional Synergy Between Rad51 and Rad54supporting
confidence: 89%
“…The ATPase and DNA supercoiling activities are up-regulated upon complex formation with Rad51 (Mazin et al 2000a;Van Komen et al 2000). Consistent with the results from the affinity pull-down experiments (Fig.…”
Section: Hed1 Ablates Functional Synergy Between Rad51 and Rad54supporting
confidence: 89%
“…The mechanism by which Rad54 protein stimulates the DNA pairing activity of Rad51 protein is different (22)(23)(24)(25)(26)(27)(28). It was found that, in contrast to other proteins that stimulate the DNA pairing activity of Rad51 protein, Rad54 protein acts at a later (synaptic) stage of DNA strand exchange (24,29).…”
mentioning
confidence: 99%
“…It was found that, in contrast to other proteins that stimulate the DNA pairing activity of Rad51 protein, Rad54 protein acts at a later (synaptic) stage of DNA strand exchange (24,29). Rad54 protein belongs to the Snf2/Swi2 group of proteins, which are involved in ATP-dependent remodeling of protein complexes, including mainly chromatin complexes (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Rad54 plays a major role in regulating the activities of Rad51. Reciprocally, the enzymatic activities of Rad54 -ATP hydrolysis, DNA supercoiling, DNA strand opening, DNA branch migration, and chromatin remodeling -are enhanced by Rad51 [9,[12][13][14]16,35]. In strains deleted for RAD54, ssDNA associated with a site-specific DSB at the MAT locus can synapse with its homologous donor sequence, but DNA strand invasion appears to be impaired [33,36].…”
Section: Introductionmentioning
confidence: 99%